Мобільний застосунок для вестибулярної реабілітації - Крамчанінов, М. О. (ХНУРЕ, 2024)
Vestibular rehabilitation is an effective method of treating diseases of the central and peripheral parts of the vestibular system. The use of VR methods allows patients to adapt to the conditions of everyday life as much as possible and return sufficient daily activity
Keywords: вестибулярна реабілітація; біомедицина